Filmmakers and financing: business plans for independents / Louise Levison - Levison, Louise
In this new and updated ultimate filmmaker’s guide , Louise Levison gives you easy- to-use steps for writing an investor-winning business plan for a feature film including: • Comprehensive explanations for each of the eight sections of a plan • Full financial section with text and tables • Sample business plan • Companion website with additional information for various chapters and detailed financial instructions ― advanced math not needed